ANALISIS PENGARUH KESEMPATAN KERJA, TINGKAT BEBAN/TANGGUNGAN DAN PENDIDIKAN TERHADAP PENGANGGURAN DI PROPINSIDATIIJAWA TENGAH - Daryono Soebagiyo; Maulidyah Indira Hasmarini; Chuzaimah Chuzaimah (Muhammadiyah University Press, 2005)
The objectives of this research are: to analyze influence of employment level, the other population burden level and the education level influences the unemployment in Central Java Province, as well as to find out how big the influence of each variable in short and long term, namely, job opportunity, the other population burden level and the education level i.e. elementary school, secondary school and high school toward unemployment in Central Java. This research was conducted in central Java, with secondary data which supported by the primary data from interviewing result with competent party.This research used Adaptive Expectancy Model as its analysis tools, namely, rationalization model which proposed by Nerlove (as in the Econometrics Gujarati book), namely, called as Stock Adjustment Model or Partial Adjustment Model (PAM)The result of this research acquired is for lower education, labor recruitment still can be done to decrease the unemployment level in the province. While for middle educational level, there is obstacle in recruitment of labors, even though; it still can be overcome because of the little relative. Yet, for the higher education, even though, in this analysis concluded that none of independent variable which used has the significant influence toward the dependent variable of unemployment, this is enabled because the higher education tends to search for the job not only in solely Central Java Province, but also they can search for the job in the other province that has leading sector of effort agreeing with that education. The higher education level is, then the lower the influence of burden level will not influence unemployment level either in short or long term is.